The Seaside Story - Robert Davis (Oz, 1989)
Most towns in America are being tom apart by the centrifugal forces of suburban sprawl. Shopping centers, subdivisions and office parks are being built on the edges of towns, connected to each other and to the town centers by increasingly overloaded roads..